Metode Penerapan Hukum Islam Berbasis Pendekatan “Empat Pola Interaksi” ala Sheikh Ali Gum'ah - Mahdin , Dr. Mahkamah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The collapse of the caliphate marked a new phase in the history of Islamic civilization. The event was accompanied by radical developments in the global reality with the birth of the revolution in telecommunications, transportation and information technology. These various developments require the birth of ijtihad products that are able to support the interests of Muslims and are able to maintain Islamic identity in the midst of these changes. The discourse on the application of Islamic law, especially in the framework of the relationship between Islam and the State in the context of the contemporary world, never seems to stop looking for answers and adequate solutions. In the context of Indonesia, for example, Pancasila as the common platform of the nation in Indonesia continues to be raised in relation to Islam. Ali Gum'ah, who is one of the members of the Al Azhar Senior Ulema Council, remapped the relationship by digging it from the historical actualization of prophethood starting from the Mecca Phase to the Medina Phase. He also raises the theory of nasakh and nasā in strengthening the vision he offers. Keywords: Islamic sharia implementation, coexistence Abstrak Runtuhnya khilafah menandai fase baru yang dalam sejarah peradaban Islam. Peristiwa tersebut dibarengi dengan perkembangan radikal dalam realitas global dengan lahirnya revolusi telekomunikasi, transportasi dan teknologi informasi. Berbagai perkembangan tersebut meniscayakan lahirnya produk ijtihad yang mampu mendukung kepentingan umat Islam dan mampu menjaga identitas keislaman di tengah arus perubahan tersebut. Diskursus tentang penerapan hukum Islam khususnya dalam kerangka relasi Islam dan Negara dalam konteks dunia kontemporer seakan tidak pernah terhenti mencari jawaban dan solusi yang memadai. Dalam konteks Indonesia misalnya, Pancasila sebagai common platform berbangsa di Indonesia masih terus diangkat dalam kaitannya dengan Islam. Ali Gum'ah, yang merupakan salah satu anggota Dewan Ulama Senior Al Azhar memetakan ulang relasi tersebut dengan menggalinya dari aktualisasi historis kenabian yang dimulai dari Fase Mekkah hingga Fase Madinah. Beliau juga mengangkat teori nasakh dan nasā dalam memperkuat visi yang ditawarkannya. Kata kunci: penerapan syariah Islam, koeksistensi